2021
DOI: 10.1177/00169862211042901
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Response to Testing in Gifted and Highly Gifted Children

Abstract: Whether intellectually gifted children have a greater emotional response when tested is still unclear. This may be due to the marked heterogeneity of this particular population, and the fact that most studies lack the power to reduce the noise associated with this heterogeneity. The present study examined the relationship between performance and emotional response in 468,423 Italian fifth-graders taking a national test on mathematics and language. Analyses were performed using statistical models with polynomia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…showing that the method can also be used in the case of the higher tail, i.e., of giftedness, despite the difficulties emerged when emotional responses to testing were considered (Cornoldi et al, 2021). Our findings, however, do not rule out the risk of a few gifted children being misdiagnosed, and clinicians should be cautious about making a differential analysis between ADHD and giftedness.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…showing that the method can also be used in the case of the higher tail, i.e., of giftedness, despite the difficulties emerged when emotional responses to testing were considered (Cornoldi et al, 2021). Our findings, however, do not rule out the risk of a few gifted children being misdiagnosed, and clinicians should be cautious about making a differential analysis between ADHD and giftedness.…”
Section: Discussionmentioning
confidence: 54%
“…Evidence is needed to show that the procedure can also be used in the case of giftedness. A study by Cornoldi, Giofrè, Mammarella, and Toffalini (2021), however, suggested that the characteristics of highly-gifted children did not match those predicted based on the general population. Specifically, the mean emotional response to testing in the population with very high achievement did not reflect the linear relationship observed between achievement score and emotional response in the general population.…”
Section: Cognitive Characteristics Of Intellectually Gifted Children ...mentioning
confidence: 92%